Developing and commercializing non-timber forest products: an Anishinaabe perspective from Pikangikum First Nation, Northwestern Ontario - Pengelly, Ryan D. (2011)
The purpose of this research was to understand an indigenous perspective on the development and commercialization of non-timber forest products, such as medicines and foods, in Pikangikum First Nation, Northwestern Ontario, Canada. Framed by a research agreement between Pikangikum First Nation and the University of Manitoba, this collaborative research was based on participant observation, field trips, semi-structured interviews, and community workshops. The appropriate development and commercialization of Anishinaabe mushkeekeeh (medicine) and meecheem (food) requires the guidance of community Elders, Anishinaabe knowledge, and traditional teachings. The community is cautiously interested in developing collaborative, diligent, and culturally respectful partnerships that interface knowledge systems. Benefit sharing means the joint ownership of intellectual property and financial benefits, developing employment and capacity-building opportunities for community members, and planning products for community use. This thesis offers a community perspective on how NTFPs might be researched, developed and commercialized in joint and mutually beneficial partnerships with a First Nation.